ANALISIS SEMIOTIK “KURSI DAN ANJING” DALAM CERPEN “SAKSI” KARYA SAPARDI DJOKO DAMONO - Pujiah Pujiah (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Literature is called meaningful language art, and literature is usually regarded as a prose that contains no fact but is fiction. One of the literary works chosen by the authors of this study is short stories. Reported from Kamus Besar Bahasa Indonesia (KBBI) states that short story is an acronym for short story. Short stories or short stories are referred to as a work of literary art that serves as a minutes of life according to (Nuroh & Sidoarjo, 2011). Similarly, the short story titled "witness" by Sapardi Djoko Damono. This research was conducted to find out the implied meaning of the short story. The method used is qualitative descriptive research method, then analyzed using a semiotic approach of Saussure thought in order to interpret the information conveyed in the short story by giving a signifier and signified so that the meaning of the short story can be known. The steps of this study are, (1) choosing short stories, (2) analyzing short stories by dividing stories into paragraphs, (3) analyzing paragraphs with Ferdinand De Saussure's semiotic theory, (4) determining markers and markers, and (5) describing results. The result of this study that became a marker is the short story and the sign is the result of the interpretation of the short story.